2010
DOI: 10.1227/01.neu.0000371729.47895.a0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Atorvastatin in an Experimental Model of Nerve Crush Injury

Abstract: BACKGROUND: Statins have therapeutic benefits for the management of several disorders. A short-term course of a high-dose statin pretreatment has demonstrated neuroprotective effects against neurological diseases. However, the molecular basis underlying the neuroprotective action of statins remains unclear. OBJECTIVE: We investigated whether a short-term course of high-dose atorvastatin pretreatment has beneficial effects in protecting sciatic nerve from crush injury. METHODS: Atorvastatin (5 mg/kg) or saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 64 publications
1
39
0
Order By: Relevance
“…7). The neuroprotective effect of simvastatin described with LSS animal model in the present study is consistent with recent reports witnessing the neuroprotection offered by statins in an experimental model of sciatic nerve crush injury (Pan et al 2010). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…7). The neuroprotective effect of simvastatin described with LSS animal model in the present study is consistent with recent reports witnessing the neuroprotection offered by statins in an experimental model of sciatic nerve crush injury (Pan et al 2010). …”
Section: Discussionsupporting
confidence: 93%
“…Although statins are mainly used to reduce cardiovascular morbidity and mortality through reducing cholesterol and low density lipoproteins levels (Igel et al 2002), recent studies have documented pleiotropic effects like anti-inflammatory, antiproliferative, antithrombic and antioxidant properties (Markovic-Plese et al 2008). Neuroprotective property of statins treatment were reported in animal models of neuroinflammatory SCI (Han et al 2011; Eroglu et al 2010; Pannu et al 2007; Pannu et al 2005), TBI (Abrahamson et al 2009; Li et al 2009; Wu et al 2010; Chauhan and Gatto 2011) and sciatic nerve injury (Pan et al 2010). Different doses of statins ranging from 1 mg/kg to 20 mg/kg body weight were tested in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Studies in an in vivo rodent model of subarachnoid hemorrhage showed that atorvastatin reduced brain caspase-3 activity and DNA fragmentation, suggesting an ability to attenuate neuronal apoptosis. 37,38 Statininduced neuroprotection has been reported in a concentration range between 100 nmol/L and 1 mmol/L within the CNS, while neuronal toxicity has only been reported at concentrations above 1 mmol/L. 39 We therefore sought to determine whether pretreatment with the commonly prescribed statin atorvastatin could attenuate neuronal damage induced by H/R insult in our global oxygen deprivation model.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the plasma samples were kept at À70 C until use. Neutrophils were purified by dextran sedimentation, then centrifuged through Ficoll-Hypaque according to our previously reported protocols [21]. Analysis of neutrophil migration was performed with a modified 24-well Transwell after the cells were labeled with calcein AM.…”
Section: Isolation and Analysis Of Blood Leukocytesmentioning
confidence: 99%